Surgical management of iatrogenic occluded left pulmonary artery. (June 2019) - Sadeghpour Tabaie, Ali; Behjati, Mohaddeseh; Mortezaeian, Hojjat; Pouraliakbar, Hamid Reza; Ghadrdoost, Behshid; Baharestani, Bahador
A 4-year-old boy developed dyspnea 18 months after attempted surgical patent ductus arteriosus closure using a clip that was inadvertently placed on the left pulmonary artery, followed by reoperation to repair the left pulmonary artery with a patch and re-close the ductus. Computed tomography angiography confirmed a large patent ductus arteriosus, left pulmonary artery occlusion, and patent left pulmonary veins. Therefore, a third surgery was performed for suture closure of the ductus and left pulmonary artery repair with an interposition tube graft. Follow-up by transthoracic echocardiography and computed tomography angiography showed good flow in the left and right pulmonary arteries.